Estudo morfométrico comparativo entre olhos com configuração daíris em platô e olhos com glaucoma primário de ângulo aberto e seiocamerular estreito - Alberto Diniz Filho (2009)
The presence of primary angle closure not related to pupillary block has been reported much more commonly than expected, particularly the plateau iris mechanism. Thus, a comparison on a morphometrical basis between eyes of patients with plateau iris configuration and eyes of patients with primary open angle glaucoma with narrow angle was made by means of a case series prospective study. Twenty eyes of 11 plateau iris configuration patients (Group 1) and 45 eyes of 27 primary open angle glaucoma with narrow angle patients (Group 2) were analyzed.The measurements of the ocular biometric parameters were taken using a keratometer, an ultrasonic pachymeter, an echo-biometer and an ultrasound biomicroscope. As a result, the eyes of Group 1 presented statistically significant higher central corneal thickness when compared to the eyes of Group 2. The eyes of Group 1 presented significantly shorter axial length than the eyes of Group 2. The eyes of Group 1 presented shallower anterior chamber in comparison to the eyes ofGroup 2. The trabecular-ciliary process distance, the iris-ciliary process distance, the iris-zonule distance and the maximum iris thickness near the pupillary edge measurements were significantly lower in Group 1. In conclusion, besides presenting shorter axial length, the eyes of patients with plateau iris configuration have an anterior segment significantly different from the anterior segment of the eyes of patients with primary open glaucoma and narrow angle. Keywords: Glaucoma, Angle-Closure. Glaucoma, Open-